Level of Knowledge of Using Cotton Bud with The Accident of Cerumen Impaction in Students of Faculty of Medicine, Palangka Raya University - Anggraini, Dwi Ria; Anugerahny, Margaretha Yayu Indah; Augustina, Indria; Surbakti, Ranintha Br; Jabal, Arif Rahman (Barigas: Jurnal Riset Mahasiswa, 2025)
The ear requires proper care to function as part of the auditory system. However, many people are unaware of maintaining ear health. A contributing factor is a lack of knowledge. Cotton buds disrupt the ear's natural cleaning mechanism by pushing earwax deeper, causing cerumen impaction. This study examined the relationship between knowledge levels and cerumen impaction using a cross-sectional approach with proportionate stratified random sampling. A total of 162 respondents were involved, including 76 students from the 2021 intake and 86 from the 2022 intake. The results showed 80 respondents (49.4%) had good knowledge, 62 (38.3%) sufficient knowledge, and 20 (12.3%) insufficient knowledge. A total of 53 respondents experienced cerumen impaction. Bivariate analysis indicated a significant relationship between knowledge level and cerumen impaction. There is a relationship between the level of knowledge and the incidence of cerumen impaction in students of the Faculty of Medicine, Palangka Raya University